2019
DOI: 10.3329/ralf.v6i2.43048
|View full text |Cite
|
Sign up to set email alerts
|

Binamasur-10, the first drought tolerant lentil variety registered in Bangladesh

Abstract: from International Centre for Agricultural Research in the Dry Areas (ICARDA) including some advanced lines from Bangladesh Institute of Nuclear Agriculture in 2006. During Preliminary Yield Trial, the genotype LG-208 produced 18.62% and 29.47% higher seed yield than the check variety BARI Masur-5 at Ishurdi and Magura respectively. Through advanced yield trials, regional yield trials, on-station and on-farm trials from 2010-11 to 2015-16, it was found that exotic germplasm LG-208 showed better performance tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Varieties which build up more vegetative growth yielded less seed, HI and vice versa. Roy et al (2019) found maximum yield of Binamasur-10 (LG-208 line) among numerous lentil accessions in Magura grown in winter. Singh and Sharma (2021) indicated that nutrient uptake significantly improved grain and biomass yield of lentil.…”
Section: Yieldmentioning
confidence: 97%
“…Varieties which build up more vegetative growth yielded less seed, HI and vice versa. Roy et al (2019) found maximum yield of Binamasur-10 (LG-208 line) among numerous lentil accessions in Magura grown in winter. Singh and Sharma (2021) indicated that nutrient uptake significantly improved grain and biomass yield of lentil.…”
Section: Yieldmentioning
confidence: 97%